Management and Quality of Clean Water in Fe (Iron) and Mn (Manganese) Parameters in Central Lempake, Samarinda, Indonesia - Nur Isnaini; Vita Pramaningsih; Ratna Yuliawati (Journal of Community Medicine and Public Health Research, 2026)
Village Lempake is a densely populated area experiencing water source pollution; therefore, the provision and management of clean water require careful consideration. This study aimed to determine the types of water sources used, assess clean water management practices, and evaluate water quality in Lempake Tengah Urban Village. A quantitative descriptive method was employed, involving the distribution of questionnaires and laboratory examination of water quality using iron (Fe) and manganese (Mn) parameters. The sample comprised 150 respondents to assess water management practices, and one water sample was collected from RT 8 for laboratory analysis. The results showed that 83% of the community used PDAM water as their primary source, 14% relied on drilled wells, 2% used dug wells, and 1% utilized mountain water sources. In terms of management practices, 81% of the community demonstrated good water management, while 19% were categorized as fair. Laboratory examination indicated that Fe levels met the established quality standard, with concentrations below 0.034 mg/L. However, Mn levels exceeded the allowable limit, with a measured concentration of 0.112 mg/L. Overall, PDAM water was the community's primary source, and water management practices were generally good. Water quality met the Fe standard but did not meet the required Mn standard. Future research is recommended to expand sampling coverage, and the community is encouraged to further improve clean water management practices.